Design and Build a Network Monitoring System at State Vocational High School 4 Bengkulu City - Vikri Julian; Reno Supardi; Aji Sudarsono (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
Internet network is a primary need in the educational environment, especially in SMK Negeri 4 Bengkulu City. SMK Negeri 4 Bengkulu City already has an internet network using the Telkom Indihome provider with a bandwidth of 30 Mbps. So far, the use of the internet is still done freely, where every user can access and connect to the internet at school. The increasing needs of internet users and the need for installed network devices result in an increased risk of damage and disruption to the internet network which causes network troubleshooting to become slower due to the absence of a system that helps to monitor and provide reports to the IT section of SMK Negeri 4 Bengkulu City when problems occur on the network. The network monitoring system at SMK Negeri 4 Bengkulu City is used to assist network operators in supervising and managing computer networks in schools. The process of monitoring the computer network is carried out within the scope of SMK Negeri 4 Bengkulu City. This study uses Zabbix as a network monitoring application that runs on the Linux Ubuntu operating system and can be accessed via a web browser. Based on the tests conducted at SMK Negeri 4 Bengkulu City, it can be concluded that the process of securing the network system can be carried out properly as expected.